(untitled) (Research, Society and Development, 2022)
Acne vulgaris, being a multifactorial infection, which can be caused by the bacterium propionibacterium acnes, often causes a nuisance to those who develop this aesthetic dysfunction. However, a safe and effective form of treatment has emerged in recent years, providing more practicality to treatments, which are called nutricosmetics. They consist of bioactive food supplements, which will combine food, cosmetics and medicine, in a capsule for oral consumption, which can be ingested once or twice a day, varying the dosage according to the concentration levels present inside the capsules. . . Based on scientific evidence, it was possible to verify that the main nutricosmetics to assist in the efficient treatment of acne vulgaris were probiotics, omega 3 and zinc. All of them have decreased lesion, anti-inflammatory effect, inhibit the action of 5-alpha reductase and are bacteriostatic. This review article, which aims to elucidate the importance of treating acne vulgaris, on the people it affects, shows that in addition to the other advantages, nutricosmetics allow the replacement of vitamins and minerals when the body has a deficit, in this way , will treat the body from the inside out, providing a better result and quality of life.